Antimicrobials in Acute Exacerbations of Chronic Obstructive Pulmonary Disease - An Analysis of the Time to Next Exacerbation Before and After Implementation of Standing Orders. (1st October 2003) - Goddard, Rob D; McNeil, Shelly A; Slayter, Kathryn L; McIvor, R Andrew
Abstract : OBJECTIVE: To compare the mean time to next exacerbation in patients with acute exacerbations of chronic obstructive pulmonary disease (COPD) before and after the implementation of standing orders. SETTING: Tertiary care hospital, Halifax, Nova Scotia, Canada. POPULATION STUDIED: The records of 150 patients were analyzed, 76 were in the preimplementation group, 74 in the postimplementation group. INTERVENTION: The management and outcomes of patients admitted with an acute exacerbation of COPD before and after the implementation of standing orders were compared. DESIGN: A retrospective chart review. MAIN RESULTS: There was no difference in the mean time to next exacerbation between treatment groups (preimplementation group: 310 days, postimplementation group: 289 days, P=0.53). Antibiotics were used in 90% of the cases (preimplementation group: 87%, postimplementation group: 93%). The postimplementation group had a 20% increase in the use of first-line agents over the preimplementation group. Overall, first-line agents represented only 37% of the antibiotic courses. CONCLUSIONS: The implementation of standing orders encouraged the use of first-line agents but did not influence subsequent symptom resolution, length of hospital stay, or the infection-free interval in patients with acute exacerbations of COPD.